Pelvic organ prolapse in women: how is it diagnosed and treated currently? - Milart, Paweł; Woźniakowska, Ewa; Czuczwar, Piotr; Woźniak, Sławomir (Menopause Review/Przegląd Menopauzalny, 2015)
The aim of the paper was to summarize the current opinions about the management of pelvic organ prolapse in women. Food and Drug Administration safety announcements from 2008 and 2011 triggered the discussion about the methods of treatment of pelvic organ prolapse and the used materials and a partial return to the methods which had been totally criticized before the implementation of meshes. The decrease in mesh usage is also observed. The studies did not demonstrate the prevalence of any particular surgical procedure. The amount of studies concerning the evaluation and the treatment of pelvic organ prolapse ensures that the quality of care provided to women with urogynecological problems is continuously increasing.